Research on Sentiment Analysis and Satisfaction Evaluation of Online Teaching in Universities During Epidemic Prevention - Zhang, Jing (Frontiers in Psychology, 2021)
Sentiment analysis of online and offline integrated teaching in universities has been widely concerned during the epidemic prevention and control normalized. Many universities have carried out online teaching activities. However, due to the lack of face-to-face teaching, the lack of emotional communication is the key problem affecting the quality of online teaching. The emotions of teachers and students in online teaching are importantly analyzed from the aspects of the transformation of teaching mode, the reconstruction of teacher-student relationship, the transmission of emotional attitude and values in this paper. Then based on the Bayesian network theory, the satisfaction of online teaching can be evaluated from the aspects of emotion analysis, learning investment and teaching interaction. Further some suggestions be put forward to improve the satisfaction of online teaching.